2016
DOI: 10.1111/jocn.13396
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with self‐care agency in patients after percutaneous coronary intervention

Abstract: Identifying factors associated with self-care agency can help healthcare professionals to consider these factors in self-care planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 14 publications
(16 reference statements)
1
12
1
3
Order By: Relevance
“…Lower socio-economic status is known to be related to a greater need for support and knowledge (Nilsson et al, 2013;Seyedehtanaz, Darvishpoor, & Saeedi, 2016). Educationally or economically disadvantaged patients may encounter inequities in health care, and financial restrictions may limit the use of health services (Artinian et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower socio-economic status is known to be related to a greater need for support and knowledge (Nilsson et al, 2013;Seyedehtanaz, Darvishpoor, & Saeedi, 2016). Educationally or economically disadvantaged patients may encounter inequities in health care, and financial restrictions may limit the use of health services (Artinian et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Patients recognised their support from family, colleagues and friends as being an important resource for future change (F alun et al, 2016). Previous evidence has shown that marriage may have a protective effect in maintaining a healthy lifestyle, possibly resulting in better overall health (Lammintausta et al, 2014;Seyedehtanaz et al, 2016). Lacking a close personal relationship increases the risk of having an acute cardiac event in both men and women, regardless of age and living as single or unmarried; moreover, it worsens the prognosis for acute coronary events (Lammintausta et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These studies indicated that higher SCAQ scores were more likely among younger and male patients compared to older and female patients, consistent with our results. Another recent study that investigated self-care agency in patients who underwent PCI similarly concluded that marital and economic status were independent predictors of higher self-care agency (Saeidzadeh et al, 2016). Further, Stamp et al (2016) observed that poor family functioning contributed to decreased self-care confidence in patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…The degree to which individuals with cardiovascular illness undertake self‐care may differ based on economic, demographic, social and educational factors 20‐22 . There is a strong focus in international guidelines on the health care team to educate and encourage the patient's self‐care behaviours as part of poststroke recovery.…”
Section: Introductionmentioning
confidence: 99%